2011
DOI: 10.1007/s12541-011-0115-7
|View full text |Cite
|
Sign up to set email alerts
|

On the size effect for micro-scale structures under the plane bulge test using the modified strain gradient theory

Abstract: A modified strain gradient theory is proposed based on the nonhomogeneity of polycrystalline metallic materials. Geometrically necessary dislocations are generated on the slip planes as well as on the grain boundary to accommodate deformation with minimum internal stress. Since amount of the geometrically necessary dislocation depends on the deformation shape, specimen size and grain size, it is an important factor for the modified strain gradient theory and the size effect. This new theory differs from the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It is well known from forming of metals that deformation under compression is highly dependent on the tribology of the loading interface, with the amount of bulging or "barrelling" being proportional to the friction coefficient. [19] It has also been shown in other studies that frictional forces oppose the development of hoop strain near the ends of cylindrical specimens while reaching a maximum at half the height. [20,21] It follows then, that the stress state near the ends of the cylinder approximate one resulting from pure hydrostatic pressure.…”
Section: Strain Measurementsmentioning
confidence: 74%
“…It is well known from forming of metals that deformation under compression is highly dependent on the tribology of the loading interface, with the amount of bulging or "barrelling" being proportional to the friction coefficient. [19] It has also been shown in other studies that frictional forces oppose the development of hoop strain near the ends of cylindrical specimens while reaching a maximum at half the height. [20,21] It follows then, that the stress state near the ends of the cylinder approximate one resulting from pure hydrostatic pressure.…”
Section: Strain Measurementsmentioning
confidence: 74%
“…The constitutive model of classical mechanics fails to accurately capture the size effect in analyzing the mechanical behavior of smallscale structures due to its lack of microscopic characteristics such as grain boundaries, defects, and material heterogeneity. Therefore, to provide a comprehensive understanding of the significant size effect observed in small-scale systems, several non-classical continuum theories, including the nonlocal elasticity theory (NET) [18,19], the modified couple stress theory (MCST) [20,21], and the modified strain gradient theory (MSGT) [22,23], have been proposed to incorporate additional length scale parameters into the analysis and enhance our ability to accurately describe the mechanical behavior of materials at micro and nano scales.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [40] found the strain gradient, which was the second derivative of displacement, played a very important role in the thin metal forming when the thickness was only several micrometres. Based on the non-homogeneity characteristics of the polycrystalline metallic materials, a modified model was proposed.…”
Section: Introduction mentioning
confidence: 99%